Vertical Distribution of Pm2.5 in Santiago de Chile Studied with an Unmanned Aerial Vehicle and Dispersion Modelling - Rubio-Campos, M; Gramsch-Labra, E; Perez-Jara, P; Olivares-Bahamondes, I; Arellano-Baeza, A; Soto-Ormeno, C (Elsevier Ltd, 2023)
The vertical structure of temperature in the troposphere is closely related to PM2.5 concentration in polluted regions, with temperature inversions associated to higher PM2.5 at the surface. This fact is more relevant in places surrounded by mountains, like Santiago de Chile, where high pollution events are common in winter. A characterization of the vertical profile of PM2.5 and temperature has been carried out in winter and spring with an unmanned aerial vehicle. Temperature inversions up to 400 m were found only in winter, with full inversions associated to the highest PM2.5 at the surface. Days with full inversion are also characterized by very low wind speeds. In most cases, PM2.5 decreased rapidly with altitude, even when there was mixing layer of considerable height. Consequently, PM2.5 above 300 m was always low, in contrast to other studies, indicating that there are factors that influence the vertical concentration of PM2.5 which are still not well understood. Chemistry transport model (CTM) simulated vertical profiles of PM2.5 agrees qualitatively well with observed concentration profiles in spring, but there is a negative bias in comparison to the measured data and also a stronger simulated vertical gradient than observed. In winter, average simulated PM2.5 concentrations at the surface are similar to observed, but with increasing altitude the simulated data decline faster than measured. © 2023 Elsevier Ltd